1994
DOI: 10.1128/mcb.14.6.4135
|View full text |Cite
|
Sign up to set email alerts
|

GPD1, which encodes glycerol-3-phosphate dehydrogenase, is essential for growth under osmotic stress in Saccharomyces cerevisiae, and its expression is regulated by the high-osmolarity glycerol response pathway.

Abstract: The yeast Saccharomyces cerevisiae responds to osmotic stress, i.e., an increase in osmolarity of the growth medium, by enhanced production and intracellular accumulation of glycerol as a compatible solute. We have cloned a gene encoding the key enzyme of glycerol synthesis, the NADH-dependent cytosolic glycerol-3-phosphate dehydrogenase, and we named it GPD1. gpdlA mutants produced very little glycerol, and they were sensitive to osmotic stress. Thus, glycerol production is indeed essential for the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
601
2
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 605 publications
(634 citation statements)
references
References 37 publications
24
601
2
7
Order By: Relevance
“…This suggests that the upregulation of genes and enzymes involved in the DHA pathway when S. cerevisiae and Z. rouxii are grown under osmotic stress conditions (Van Zyl et al, 1991;Rep et al, 2000;Iwaki et al, 2001) might play an important role in the response of yeasts to osmotic stress. As previously reported (Albertyn et al, 1994), the intracellular glycerol concentration in S. cerevisiae increases significantly in response to hyperosmotic stress (Table 1). Similar intracellular glycerol levels were found in the three strains under hyperosmotic stress, whereas the level under nonosmostress conditions in the S. cerevisiae dak1 dak2 strain carrying the DAK1 gene of S. cerevisiae was significantly lower than in the other two strains, possibly due to the different vectors used (Table 1).…”
Section: Functional Analysis Of Z Rouxii Dak1 In S Cerevisiae Dak1 supporting
confidence: 85%
See 2 more Smart Citations
“…This suggests that the upregulation of genes and enzymes involved in the DHA pathway when S. cerevisiae and Z. rouxii are grown under osmotic stress conditions (Van Zyl et al, 1991;Rep et al, 2000;Iwaki et al, 2001) might play an important role in the response of yeasts to osmotic stress. As previously reported (Albertyn et al, 1994), the intracellular glycerol concentration in S. cerevisiae increases significantly in response to hyperosmotic stress (Table 1). Similar intracellular glycerol levels were found in the three strains under hyperosmotic stress, whereas the level under nonosmostress conditions in the S. cerevisiae dak1 dak2 strain carrying the DAK1 gene of S. cerevisiae was significantly lower than in the other two strains, possibly due to the different vectors used (Table 1).…”
Section: Functional Analysis Of Z Rouxii Dak1 In S Cerevisiae Dak1 supporting
confidence: 85%
“…When the S. cerevisiae dak1 dak2 strain overexpressing the ZrDAK1 gene was cultivated under osmotic stress conditions (50 g/l NaCl), the generation time was 0.185/h, whereas in the absence of osmotic stress, the generation time was 0.180/h. This result was surprising, since the growth of S. cerevisiae grown on glucose is usually reduced significantly in the presence of 50 g/l NaCl (Albertyn et al, 1994). This suggests that the upregulation of genes and enzymes involved in the DHA pathway when S. cerevisiae and Z. rouxii are grown under osmotic stress conditions (Van Zyl et al, 1991;Rep et al, 2000;Iwaki et al, 2001) might play an important role in the response of yeasts to osmotic stress.…”
Section: Functional Analysis Of Z Rouxii Dak1 In S Cerevisiae Dak1 mentioning
confidence: 99%
See 1 more Smart Citation
“…Gpd1p is an enzyme required for glycerol synthesis and mRNA level of GPD1 is upregulated by high osmotic stress. 18 Phosphorylation of Cdc37p is important in the high osmotic stress signal transduction pathway that leads to glycerol synthesis. 19 Therefore, increase of levels of Gpd1p and phosphorylated Cdc37p by BcA treatment suggested that BcA might affect the high osmotic stress signal transduction pathway by increasing Cdc37p phosphorylation.…”
Section: Effects Of Bca On Gene Transcriptionmentioning
confidence: 99%
“…Glycerol-3-phosphate is further dephosphorylated to glycerol by glycerol-3-phosphatase, which includes two homologs encoded by HOR 1 and HOR 2 in S. cerevisiae (Hirayama et al 1995, Norbeck et al 1996). Gene replacement of the two homologous genes namely GPD 1 and GPD 2 resulted in mutants with a decreased accumulation of intracellular glycerol and increased sensitivity to osmotic stress as compared to wild-type in S. cerevisiae (Albertyn et al 1994). However, activities of GPD could not be detected during appressorium maturation, raising the possibility of an alternative glycerol production route needed to build up turgor pressure for appressorium penetration (Thines et al 2000a).…”
Section: The Essential Role Of Glycerol Production In Appressorium Fumentioning
confidence: 99%